2012
DOI: 10.1128/mcb.06159-11
|View full text |Cite
|
Sign up to set email alerts
|

Role of AMPK-mTOR-Ulk1/2 in the Regulation of Autophagy: Cross Talk, Shortcuts, and Feedbacks

Abstract: Living cells are adaptive self-sustaining systems. They strictly depend on the sufficient supply of oxygen, energy, and nutrients from the outside in order to sustain their internal organization. However, as autonomous entities they are able to monitor and appropriately adapt to any critical fluctuation in their environment. In the case of insufficient external nutrient supply or augmented energy demands, cells start to extensively digest their own interior. This process, known as macroautophagy, comprises the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
969
3
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 1,212 publications
(1,049 citation statements)
references
References 123 publications
25
969
3
7
Order By: Relevance
“…Recent studies have addressed a new mechanism for the control of mammalian autophagy by AMPK that AMPK regulates autophagy through direct phosphorylation of ULK1 (Alers et al ., 2012). To determine the role of AMPK activation in the effect of β‐GPA on lifespan in Drosophila , compound C (an AMPK inhibitor) and RNA interference were employed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have addressed a new mechanism for the control of mammalian autophagy by AMPK that AMPK regulates autophagy through direct phosphorylation of ULK1 (Alers et al ., 2012). To determine the role of AMPK activation in the effect of β‐GPA on lifespan in Drosophila , compound C (an AMPK inhibitor) and RNA interference were employed.…”
Section: Resultsmentioning
confidence: 99%
“…Our study showed that the elevated levels of autophagy and lifespan extension induced by β‐GPA were abolished by Atg1‐RNAi. ULK1/Atg1‐dependent autophagy is regulated by the mammalian target of rapamycin complex 1 (mTORC1) and AMPK (Alers et al ., 2012). Notably, the activity of ULK1/Atg1 kinase increases in an AMPK‐dependent manner following glucose deprivation (Alers et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations